Education Transformation Model of Traditional Pesantren in Aceh Province of Indonesia - Mukhlisuddin Ilyas; Zahrila Ismail; Fitri Zulfidar; Syarfuni Syarfuni; Masrizal Masrizal (STAI Hubbulwathan Duri, 2022)
This research explains that since Indonesia's establishment, Pesantren has demonstrated its ability to adapt to changing educational models as the embryo of the education model. During the transition of the educational model, this institution served as a grass-roots institution that provided basic education to people at all levels. Pesantren is competitive in assuring the development of a model of the education system that competes with the numerous models offered by other modern educational institutions. The Pesantren transformation model was examined using qualitative analysis in this study. Concrete data demonstrates that Pesantren as an Islamic institution has matured, with a wide range of options that contribute to the creation of pesantren's basic values as the spirit and culture of Indonesia. The result revealed that Pesantren, an Islamic educational institution, was developed and capable of competing in the face of education transformation needs.